IRON DEFICIENCY, ANEMIA AND QUALITY OF LIFE OF CELIAC DISEASE PATIENTS - REVIEW - Kinga Kosiec-Stolarek; Oliwia Krzemień; Iga Kwiecień; Agnieszka Raczyńska; Natalia Pacocha; Jakub Jędrychowski; Natalia Karpowicz; Julia Kaszucka; Małgorzata Krzyżanowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction Celiac Disease (CD) is a chronic autoimmune disease that causes damage to the small intestine in reaction to a specific protein - gluten. One of the most common complications of CD is iron deficiency, which leads to anemia. Iron deficiency anemia (IDA) has a significant effect on a patient’s health, both physical and mental, vastly impairing quality of life. This paper provides mechanisms leading to iron deficiency and its impact on the development of the IDA; clinical symptoms, diagnostics, and treatment of iron deficiency. It also highlights the importance of early diagnosis and the necessity of strictly following a gluten-free diet. Materials and Methods This review uses resources available in the PubMed and Google Scholar databases. A thorough search of English-language articles involved key terms: „celiac disease”, „iron deficiency”, „iron deficiency anemia”, „gluten-free diet”, „quality of life”. The information obtained through these searches has been compiled and examined. Results Research indicates that iron deficiency anemia is a prevalent complication in patients with CD. In case of a non-responsive form of IDA, it is important to exclude the possibility of CD. Once CD with IDA is detected, restoring iron stores to the desired level, as well as implementing a gluten-free diet on a permanent basis is required. Conclusions Studies show the close connection between CD, IDA, and the impaired quality of patients’ lives, emphasizing the role of early diagnosis and subsequent implementation of a gluten-free diet. Further interdisciplinary research on methods of diagnosis and treatment are vital for the advancement of medical care and the well-being of patients.